Financial Market Dynamics in an Enlarged European Union - Dimitris Kenourgios; Aristeidis Samitas; Nikos Paltalidis (Journal of Economic Integration, 2009)
This paper provides evidence of integration in European equity and bond markets over the period January 2, 1997 to October 1, 2006. Our focus is to examine time-varying correlation dynamics in Euro-area, Central European (CE) and Balkan financial markets, modifying the asymmetric generalized dynamic conditional correlation (AG-DCC) model developed by Cappiello, Engle and Sheppard (Journal of Financial Econometrics, 2006). Using structural breaks, we identify the optimal time decay where financial markets share highest comovement. The results show an increase in the level of dependence during the period of the internet bubble collapse (2000), the Balkan countries start formally discussions to join European Union (2000), the introduction of Euro banknotes and coins (2002) and the entry of CE countries in EU (2004). The CE European and Balkan countries become gradually more integrated with the EMU countries, which is consistent with the interpretation that these countries may be expected to join the Euro in the future.